Working with Older Adults: Predictors of Attitudes Towards Ageing in Psychology and Social Work Students, Faculty, and Practitioners. (December 2014) - Chonody, Jill M; Webb, Stephanie N; Ranzijn, Rob; Bryan, Janet
<x xml:space="preserve">Abstract</x> The Australian population is experiencing a rapid ageing of the population, and as such, an increased need for gerontological practitioners in the helping professions will continue to grow. Terror management theory (TMT), which was used to frame this study, posits that because of the fact that humans are aware of their own mortality, they are compelled to avoid the anxiety associated with it. Personal ageing and interaction with older adults may be reminders of the unavoidable decline and death that faces us all. The purpose of this study is to examine comfort in spending time with older adults amongst students, academic teaching staff, and practitioners in the fields of psychology and social work. We sought to determine if TMT helped predict fear of being with older adults. Ageism, contact with older adults, and known demographic factors associated with attitudes towards older adults were also examined. Hierarchical multiple regression explained nearly 46% of the variance in comfort with older adults and indicated that fear of ageing, positive ageism, negative ageism, contact with older adults, and sex were significant predictors. Educational efforts aimed at addressing beliefs about ageing and older adults may contribute to further comfort in working with older adults.